Application of the World Health Organization Programmatic Assessment Tool for Risk of Measles Virus Transmission—Lessons Learned from a Measles Outbreak in Senegal. Issue 9 (11th June 2015) - Harris, Jennifer B.; Badiane, Ousseynou; Lam, Eugene; Nicholson, Jennifer; Oumar Ba, Ibrahim; Diallo, Aliou; Fall, Amadou; Masresha, Balcha G.; Goodson, James L.
Abstract : The World Health Organization (WHO) African Region set a goal for regional measles elimination by 2020; however, regional measles incidence was 125/1, 000, 000 in 2012. To support elimination efforts, the WHO and U.S. Centers for Disease Control and Prevention developed a tool to assess performance of measles control activities and identify high‐risk areas at the subnational level. The tool uses routinely collected data to generate district‐level risk scores across four categories: population immunity, surveillance quality, program performance, and threat assessment. To pilot test this tool, we used retrospective data from 2006 to 2008 to identify high‐risk districts in Senegal; results were compared with measles case‐based surveillance data from 2009 when Senegal experienced a large measles outbreak. Seventeen (25%) of 69 districts in Senegal were classified as high or very high risk. The tool highlighted how each of the four categories contributed to the total risk scores for high or very high risk districts. Measles case‐based surveillance reported 986 cases during 2009, including 368 laboratory‐confirmed, 540 epidemiologically linked, and 78 clinically compatible cases. The seven districts with the highest numbers of laboratory‐confirmed or epidemiologically linked cases were within the capital region of Dakar. All except one of these seven districts were estimated to be high or very high risk, suggesting that districts identified as high risk by the tool have the potential for measles outbreaks. Prospective use of this tool is recommended to help immunization and surveillance program managers identify high‐risk areas in which to strengthen specific programmatic weaknesses and mitigate risk for potential measles outbreaks.